2014
DOI: 10.1097/mph.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life of Egyptian Children With Immune Thrombocytopenia and Their Parents

Abstract: Health-related quality of life has been recognized as an important pediatric outcome measurement. Kid's ITP Tool was used to measure health-related quality of life of 80 Egyptian children with immune thrombocytopenia and their parents in relation to different disease parameters. A positive correlation between scores of child/proxy reports and parent report was found. Patients with newly diagnosed immune thrombocytopenia had significantly lower scores of both child/proxy reports and parent reports than chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
12
2
Order By: Relevance
“…No differences were found in HRQoL scores between children with skin bleeding only and children with mucosal bleeding as well. These results are comparable to those of the study by Neunert et al 6 , but contrast with those of the study by Mokhtar et al 11 The latter difference could be attributed to the different bleeding score used as well as to the different ethnic and cultural background of their study population.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…No differences were found in HRQoL scores between children with skin bleeding only and children with mucosal bleeding as well. These results are comparable to those of the study by Neunert et al 6 , but contrast with those of the study by Mokhtar et al 11 The latter difference could be attributed to the different bleeding score used as well as to the different ethnic and cultural background of their study population.…”
Section: Discussioncontrasting
confidence: 56%
“…This result seems to contrast with those of the study by Zilber et al, who did not find any differences in scores between acute and chronic ITP patients 8 and the studies by Mokhtar et al 11 and Klaassen et al, 24,25 who found higher KIT scores in patients with chronic disease compared to those in patients with newly diagnosed ITP. However, the prospective design of our study seems to be better suited to answer this study question than the cross-sectional design of the studies by Zilber et al, Mokhtar et al and Klaassen et al There are several potential explanations for the higher KIT parent self-report and proxy report scores we observed in children with ITP who recovered.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Additional disease burdens include medication side effects, persistence of disease, fatigue, and restrictions on activity. Since the validation of the Kids’ ITP Tools (KIT) nearly a decade ago, health‐related quality of life (HRQoL) in childhood ITP has become an important patient‐centered outcome assessed in prospective trials …”
Section: Introductionmentioning
confidence: 99%